"I Am a Muslim First …" Challenges of Muslimness and the UK State Schools. Issue 3 (3rd July 2019) - Shah, Saeeda
ABSTRACT: When a third-generation, British-born young Muslim student in a British state school says to researcher "I am a Muslim first …, " it makes one think. What are the factors underpinning this statement? In a highly diverse multi-faith, multiethnic, multicultural society such as Britain, why does a young British Muslim student become so emphatic in proclaiming faith identity? The article looks into identity dynamics with a focus on Muslim youth in the UK and discusses how these might impact on their educational experiences. The article also explores the challenges facing educational leaders in managing Muslimness.